A range extension of Heterocladium flaccidum (Schimp.) A.J.E.Sm. to Africa and Asia and confirmation of its specific individuality - (:unkn) unknown (My University, 2020)
Recent collections of Heterocladium flaccidum in Tunisia and in Georgia (Caucasus) represent the first records of this species both in Africa and Asia. Molecular phylogenetic analysis of samples from France, Great Britain, Tunisia and Georgia placed the species in a maximally supported clade sister to or nested in other species of Heterocladium s.str., i.e. excluding recently segregated Heterocladiella species. This genetic distinction of H. flaccidum from H. heteropterum, found in separate analyses of ITS and trnL-F markers, strongly supports the specific recognition of H. flaccidum. Representative African and Asian specimens are illustrated and described. Ecological and chorological details are provided.
Keywords: African Research